Calculating PI Related Indices and Its Polynomial of Hyaluronic Acid and Conjugates - S. Subramanian; P. Rajesh; P. Kandan (IndoMS, 2022)
A large number of medical experiments have confirmed that the features of drugs have a close correlation with their molecular structure. Drug properties can be obtained by studying the molecular structure of corresponding drugs. The calculation of the topological index of a chemical graph enables scientists to have a better understanding of the physical chemistry and biological characteristics of drugs. In this paper, we focus on Hyaluronic Acid-Curcumin/Paclitaxel conjugate which are widely used in the manufacture of anticancer drugs. Therefore in this paper we have computed the Padmakar-Ivan related indices and its polynomial of the Hyaluronic Acid-curcumin/paclitaxel conjugate by using edge partitioning technique.